Study the morphological changes and histological lesions that induced by shigella flexneri for liver in mice and the role of camel's milk and antibiotic to treatment - Khalid Hameed Ali, Aziz; Hyssein Amin, Shereen (Tikrit Journal of Pharmaceutical Sciences, 2023)
The present study demonstrated the morphological changes and histological lesions in the liver of albinomice Mus musculus induced per oral infection of (Shigella flexneri). The aim of the study is to assesstreatment by used camel milk and antibiotic Ciprofloxacin and the effect of camel milk and antibiotic oninfected organs. Also study the inhibition efficacy of milk in vivo. The study tested sensitive of Shigellaflexneri toward group from antibiotics, the results showed that the bacteria sensitive for (Ciprofloxacin,Neomycin, Amikacin) and resistance for (Ampicillin, Cefixin, Clindamycin, Vancomycin, Tetracyclin,Erythomycin, Ceftriaxone). Also test the inhibition efficacy of camel milk toward this bacteria andobvious that this bacteria very sensitive for camel milk. The present study used 32 mice that dividerandomly to eight groups (each group consist 4 mice), the first group was control group administratedonly normal diet and water, the second group administrated lethal dose for 50% of animals, the thirdgroup administrated infected dose from bacteria, but (3, 4, 5, 6, 7) groups administrated infected dosefrom bacteria and treated with camel milk with doses (0.25, 0.5, 1 ml and with ad libitum), the eighthgroup administrated infected dose from bacteria and treated with antibiotic (concentration 0.125 mg/ kg).The microscopic examination showed many lesions in liver for groups that treated with lethal andinfected dose from Shigella flexneri. This lesion appeared as vacuolated and focal necrosis ofhepatocytes, hemorrhage and congestion was appeared, infiltration of inflammatory cells betweenhepatocytes. This lesions appeared more sever in the groups administrated with lethal dose. Thehistological lesions in groups that administrated with bacteria and treatment with camel milk presentedenhancement in the arrangement of hepatocytes and less necrosis, degeneration, hemorrhage andinfiltration of inflammatory cells especially in the groups which was treated with open dose of camelmilk. The group which was treated with antibiotic alone, microscopic examination showed enhancementin liver compared with groups that administrated with lethal and infected dose but that less efficiencycompared with camel milk.